A TRANSITIVITY ANALYSIS OF GRETA THUNBERG’S 2019 CLIMATE ACTION SUMMIT SPEECH - Ardelia Karisa; Stefanny Lauwren (University of Muhammadiyah Malang, 2020)
Climate change has been one of the most significant concerns for the United Nations. As a result, the United Nations held a summit in 2019, inviting several notable speakers in the field. One of them is a young teenager from Swedish, Greta Thunberg. Greta Thunberg is a prominent climate activist who delivered a speech at the United Nations Climate Action Summit 2019, which is about how people and the government need to limit global warming. Her address became viral and garnered attention from many media, and roused a massive youth-led climate rally. Thus, this study analyzed her speech as the object of the study and employed a descriptive qualitative method. The study scrutinized 54 clauses through transitivity analysis from Hallidayan Systemic Functional Grammar (SFG) to understand the processes in the address and its function. This current study has revealed that the speaker’s dominantly used material process (37%) to describe the damage to the environment done by people. The use of relational process (31.5%) describes climate change's effects on the world and her life. The mental process used in 16.7% of the data provokes guilt and responsibility, as she pointed the audience as the actors that cause climate change. The behavioural process (7.4%) shows that Thunberg will not stay quiet on climate crisis when her generation is the one who will suffer from it. Existential process (3.7%) is used to describe the existing problems, while verbal process (3.7%) is used in quoting the high-profile politician to prove that none of their promises have been fulfilled.